Presence of early stage cancer does not impair the early protein metabolic response to major surgery. Issue 3 (16th January 2017) - Engelen, Mariëlle P.K.J.; Klimberg, V. Suzanne; Allasia, Arianna; Deutz, Nicolaas EP
Abstract: Background: Combined bilateral mastectomy and reconstruction is a common major surgical procedure in women with breast cancer and in those with a family history of breast cancer. As this large surgical procedure induces muscle protein loss, a preserved anabolic response to nutrition is warranted for optimal recovery. It is unclear whether the presence of early stage cancer negatively affects the protein metabolic response to major surgery as this would mandate perioperative nutritional support. Methods: In nine women with early stage (Stage II) breast malignancy and nine healthy women with a genetic predisposition to breast cancer undergoing the same large surgical procedure, we examined whether surgery influences the catabolic response to overnight fasting and the anabolic response to nutrition differently. Prior to and within 24 h after combined bilateral mastectomy and reconstruction surgery, whole body protein synthesis and breakdown rates were assessed after overnight fasting and after meal intake by stable isotope methodology to enable the calculation of net protein catabolism in the post‐absorptive state and net protein anabolic response to a meal. Results: Major surgery resulted in an up‐regulation of post‐absorptive protein synthesis and breakdown rates ( P  < 0.001) and lower net protein catabolism ( P  < 0.05) and was associated with insulin resistance and increased systemic inflammation ( P  < 0.01). Net anabolic response to the meal was reduced after surgery ( P  < 0.05) but higher in cancer ( P  < 0.05) indicative of a more preserved meal efficiency. The significant relationship between net protein anabolism and the amount of amino acids available in the circulation ( R 2  = 0.85, P  < 0.001) was independent of the presence of non‐cachectic early stage breast cancer or surgery. Conclusions: The presence of early stage breast cancer does not enhance the normal catabolic response to major surgery or further attenuates the anabolic response to meal intake within 24 h after major surgery in patients with non‐cachectic breast cancer. This indicates that the acute anabolic potential to conventional feeding is maintained in non‐cachectic early stage breast cancer after major surgery.